PELATIHAN SOFTWARE WINGEOM UNTUK MENINGKATKAN KOMPETENSI GURU DI KECAMATAN PANGALENGAN - Risma Amelia; Harry Dwi Putra; Ratna Sariningsih (Abdimas Siliwangi, 2021)
Community service is conducted in the form of a training workshop on the use of wingeom software for elementary, junior and senior high school teachers in Pangalengan District. The purpose of this service is to improve teacher competence in using learning software in the classroom, especially wingeom software. The location of the service was held at SMAN 1 Pangalengan, with a total of 51 participants. Researchers conducted initial observations by distributing questionnaires on the google form. The results of preliminary observations indicate that teachers in schools are still lacking in the use of ICT, especially mathematical software in learning. The teachers do not have the skills to use the software in learning mathematics. The lack of use of ICT is due to the teachers' lack of understanding of ICT, so that teachers have difficulty in operating mathematical software. This has encouraged the implementation team to conduct wingeom software training to improve the competence of teachers in the ICT field in Pangalengan District. During the wingeom software training, the teachers were very enthusiastic in following their activities from the beginning to the end of the training. Through the questionnaire at the end of the training it was found that the teachers could master the wingeom software and be able to apply the software when learning especially learning about geometry. Wingeom software training can improve the competence of teachers in Pangalengan District. Through this mathematics software training, the teacher has skills n teaching mathematics that is interesting and fun for students.